The Effect of Counseling Using Puzzle on Oral Health Knowledge of 3rd and 4th Grade Students of SD Negeri 2 Cikidang - Riski Amalia Hidayah (Kesmas Indonesia, 2023)
Dental health problems often occur in elementary school children. According to WHO, 60% -90% of children worldwide have experienced caries. Dental caries is caused by multifactorial one of which is the lack of knowledge of oral health. To improve knowledge about children's oral health by way of counseling using media puzzles because it is an interesting media education. The aim of this study was to determine the effect of media counseling on oral health knowledge in 3rd and 4th grade students of SD Negeri 2 Cikidang. This type of research is pre-experimental, with a one-group pretest-posttest research design with 32 students as respondents. The data is processed by the Wilcoxon test because the data distribution is not normal. The average value of knowledge before counseling was 63.4, while after counseling was 75.6. The results of the Wilcoxon test (p = 0.000) which statistically showed differences in the understanding of oral and dental health knowledge before and after counseling. The counseling method with puzzles can increase the knowledge of dental and oral health of grade 3th and 4th students at SDN 2 Cikidang. The students have a level of knowledge both before and after counseling